Activities of beekeeping societies in the territory of Ukraine at the end of the 19th – beginning of the 20th century - Chalavan, Victor (Ukrainian Peasant, 2024)
The purpose of the article is to analyze the activities of beekeepers’ associations on Ukrainian territory in the 19th and early 20th centuries and assess their contribution to the development of the industry through initiatives related to the practice of beekeeping, scientific and informational support, influence on the development of government policy vectors, etc. The scientific novelty of the study consists in deepening and systematizing information about the activities of beekeeping societies based on a detailed analysis of industry periodicals of the late 19th and early 20th centuries: «Bulletin of the Russian Beekeeping Society», «Bulletin of the South Russian Animal Husbandry», «Voice of the Beekeeper», «Notes of the Simferopol Department of the Imperial Russian Horticultural Society», «Russian Beekeeping Leaflet», «Southern Farm», «South Russian Agricultural Newspaper». Conclusions. It was established that by the mid-1910s, beekeeping had turned into an important branch of agriculture, which gave the country a certain economic profit, although not all regions of the Russian Empire could boast of the introduction of rational beekeeping. A network of beekeepers’ associations, demonstration and educational apiaries has been created. There was an urgent need to establish a special research institution for beekeeping, the main task of which would be the organization of systematic scientific work, experiments and observations, the introduction of rational practical beekeeping and the dissemination of comprehensive knowledge about the practice and theory of beekeeping, and would prepare a sufficient contingent of specialists. The merit of the beekeeping societies was in systematic requests to the government for the establishment of special lower practical beekeeping schools, teaching of this subject in secondary and higher agricultural educational institutions, as well as for the need to hold periodic courses and exhibitions, distribution of model apiaries. The public, through the beekeepers’ associations, took care of the spread of beekeeping knowledge among the population - through educational institutions, model and training apiaries, mobile and stationary museums and exhibitions, courses, public lectures, activities of private and state instructors, etc. The collection of statistics on beekeeping throughout the Russian Empire was organized. The opening of honey-making schools and the removal of excise duties on honey, beverages and sugar for feeding bees, the reduction of the cost of beekeeping equipment, the so-called «honey Sundays» began to be organized as a means of popularizing and selling honey, as well as as a means of combating its falsification; a proposal was put forward to organize analyzes of beekeeping products in city medical and sanitary laboratories and in laboratories of educational institutions in order to prevent the spread of fakes. While engaged in scientific and research activities, the members of the societies actively studied bee diseases, in particular, blight, and measures to combat them. A program of a network of industry research stations in the empire was developed.